Spatio-temporal pattern and allocation efficiency of public service land in rural settlements - Zheng, Qiuyue; Jiang, Guanghui; Tian, Yaya; Meng, Liang; Yang, Lei (Frontiers in Environmental Science, 2022)
The construction of infrastructure and public services is the core of countryside planning. As the carrier of rural public services, the evolutionary pattern and efficiency of rural public service land (RPSL) can directly reflect the development of rural public services. However, existing studies have mainly characterized public service space through the number of public service facilities rather than the area of land occupied. Furthermore, research on public service land in rural settlements is lacking. Taking 273 villages in the Pinggu District of Beijing as an example, this article integrated multi-dimensional data, including geospatial data, big data, and socio-economic data, to analyze the spatio-temporal evolution characteristics of RPSL from 2004 to 2019. The bi-dimensional allocation efficiency index addressing qualitative and quantitative development was introduced to measure the allocation efficiency of RPSL. The results show that the area of RPSL in Pinggu District has increased by 57.28 ha, and the internal land use structure of RPSL has become balanced. The evolution pattern of RPSL was characterized by both agglomeration and dispersion, as well as by a significant tendency to expand along main roads. The uneven distribution of public service facilities and the significant differences in accessibility reflected the non-equalization of public services. The allocation efficiency of RPSL in 79.23% of the villages was at a low level, which is mainly due to the mismatch between the rural public service land area and the population, the non-differentiated allocation of public service facilities, the uneven public service quality, and the low accessibility of RPSL. In the future, policymakers should plan rural public service land rationally from the perspective of the actual situation, such as setting flexible indicators, building a living circle of rural settlements, and so on. This research will not only enrich the research perspective of rural public services but also provide a reference for the study on the utilization and optimization of rural settlements.